2019
DOI: 10.3390/ijms20153742
|View full text |Cite
|
Sign up to set email alerts
|

Aphid-Triggered Changes in Oxidative Damage Markers of Nucleic Acids, Proteins, and Lipids in Maize (Zea mays L.) Seedlings

Abstract: Prior experiments illustrated reactive oxygen species (ROS) overproduction in maize plants infested with bird-cherry-oat (Rhopalosiphum padi L.) aphids. However, there is no available data unveiling the impact of aphids feeding on oxidative damages of crucial macromolecules in maize tissues. Therefore, the purpose of the current study was to evaluate the scale of oxidative damages of genomic DNA, total RNA and mRNA, proteins, and lipids in seedling leaves of two maize genotypes (Złota Karłowa and Waza cvs—susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 64 publications
1
24
1
Order By: Relevance
“…(highly resistant). Similarly, Sytykiewicz et al [ 22 ] elucidated that R. padi aphid infestation caused up to two times higher accumulation of MDA in maize leaves of susceptible Złota Karłowa cv., compared to more resistant Waza cv., and the highest increments at 24 h were noted. In addition, at this time point of the aphid infestation occurred the highest degree of the electrolyte leakage (indicating disruption of plasma membrane) in relation to the control.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(highly resistant). Similarly, Sytykiewicz et al [ 22 ] elucidated that R. padi aphid infestation caused up to two times higher accumulation of MDA in maize leaves of susceptible Złota Karłowa cv., compared to more resistant Waza cv., and the highest increments at 24 h were noted. In addition, at this time point of the aphid infestation occurred the highest degree of the electrolyte leakage (indicating disruption of plasma membrane) in relation to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Short-time increments in ROS level in the host tissues are linked to plant innate immunity responses toward adverse environmental stimuli; however, tolerance of the plant systems to long-term exposure to excessive ROS amounts is essential to maintain the functioning of numerous physiological processes. Our recent studies [ 20 , 22 ] demonstrated a significant increase in level of several biochemical markers of the oxidatively-induced damages of total and mRNAs, proteins and lipids in the aphid-stressed maize plants. Łukasik and Goławska [ 20 ] reported an increase in the content of malondialdehyde (MDA; biomarker of lipid peroxidation) in M. dirhodum -stressed seedlings of Ambrozja and Płomyk maize cvs, and the highest level of this compound at 48–96 h was recorded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations